LYVE-1 and hyaluronan - a molecular velcro - Lawrance, W (2013)
The lymphatic system comprises a network of vessels whose primary functions are the maintenance of extracellular fluid balance and the transport of antigen-presenting cells from the periphery to the lymph nodes, thus facilitating immunological surveillance of the tissues and activation of adaptive immunity. In malignant disease, the lymphatics are both a route for dissemination and a reservoir for metastatic cancers such as cutaneous melanoma and breast carcinoma, where lymph node involvement is an early indicator of prognosis. Yet, despite such obvious importance in disease, the fundamental biology of the lymphatics is poorly understood and critical mechanisms such as those underlying trafficking of dendritic and tumour cells have been largely overlooked. The focus of this thesis is lymphatic vessel endothelial hyaluronan receptor LYVE-1, and the regulation of its binding to the extracellular matrix glycosaminoglycan, hyaluronan (HA). Found selectively on the surface of lymphatic vessels, but sharing many of the features of the leukocyte homing receptor CD44, LYVE-1 appears a likely candidate for regulation of lymphatic trafficking during the stage at which cells migrate into the vessel. However, the precise function of LYVE-1 in recent years has remained enigmatic, not least because the native receptor is subject to post-translational modification with sialic acid, with the effect that HA binding is inhibited in lymphatic endothelium. The results of this thesis demonstrate that sialylation of LYVE-1 is not a short term regulatory modification, but rather a longer term mechanism that imposes a requirement for higher order receptor complex formation or HA crosslinking to achieve stable binding. This implies that native LYVE-1 is an active HA binding protein even when sialylated, with implications for our understanding of the role played by the receptor in HA uptake and metabolism, and transmigration of lymphatic endothelium by migratory leukocytes. Like CD44, HA binding to LYVE-1 is dependent on multivalent interactions between receptor and ligand, and may be enhanced by processes that increase the avidity of the interaction. Here for the first time it is shown that the native LYVE-1 molecule on lymphatic endothelium may be activated to bind HA following clustering of the receptor, or presentation of HA in a cross-linked form, such as that resulting from incubation with the HA binding protein TSG-6.